2016
DOI: 10.18203/2320-6012.ijrms20164566
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in pediatric seizures

Abstract: Background: Accurate etiological diagnosis of seizures in children is important to begin an effective treatment. MRI is an excellent neuroimaging tool that is highly accurate. It helps in diagnosis, determining the treatment protocol and predicting the outcome. Dedicated studies in paediatric population using MRI brain have been even fewer till date in India. Current study aims to find the common etiology of pediatric seizures on MRI in a developing country like India.Methods: Hospital based retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
3
7
0
Order By: Relevance
“…Our findings are similar to that of a study conducted by Kramer et al (1988) which detected neuroimaging abnormalities in 35% of patients [24]. Our study results are also consistent with a study done by Sahdev et al (2016) which revealed abnormal neuroimaging in 31.4% cases while in 68.6% of cases no abnormality was seen [1] However in a study conducted by Gulati et al (1991), the study revealed abnormal neuroimaging in 92.9% of the cases [13].…”
Section: Table-2: Statistical Significance Of the History Of Birth Assupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are similar to that of a study conducted by Kramer et al (1988) which detected neuroimaging abnormalities in 35% of patients [24]. Our study results are also consistent with a study done by Sahdev et al (2016) which revealed abnormal neuroimaging in 31.4% cases while in 68.6% of cases no abnormality was seen [1] However in a study conducted by Gulati et al (1991), the study revealed abnormal neuroimaging in 92.9% of the cases [13].…”
Section: Table-2: Statistical Significance Of the History Of Birth Assupporting
confidence: 93%
“…These results are similar to that of a study conducted by Shadev et al which also did not detect any brain tumor [1]. However, these results are different from that of the study conducted by Chaurasia et al (2013) which revealed a brain tumor in 4 (2.1%) cases [25].…”
Section: Table-2: Statistical Significance Of the History Of Birth Assupporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, imaging is critical to potentially identifying the aetiology of seizure activity and guiding therapy. [9][10][11] This study describes the spectrum of abnormal MRI findings in paediatric seizure disorder using a low-field MRI system and highlights the relative usefulness of this procedure in paediatric seizure imaging, evaluation and management.…”
Section: Magnetic Resonance Imaging (Mri) Positronmentioning
confidence: 99%